STATUS KEBERLANJUTAN BUDIDAYA SAYURAN HIDROPONIK DI KOTA PADANG SUMATERA BARAT - Rika Yulia Putri; Mia Rosmiati; Wawan Gunawan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Vegetables have crucial benefits in meeting the needs of food consumption and human nutrition. The demand for hydroponic vegetable commodities continues to increase every year such as vegetable needs in Padang City. The purpose of the study is to see the sustainability status of hydroponic vegetable cultivation in Padang City, West Sumatra supported economic, social, ecological, technical, institutional, and multidimensional dimensions. The information is obtained through multidimensional scaling (MDS. The result showed the sustainability status of the cultivation of hydroponic vegetables in Padang City, West Sumatra based on an overall (multidimensional) analysis features a value  of 49,13% which is quite sustainable. The results of every dimensions analysis showed that the economic and institutional dimensions of 51,07% and 42,15% respectively, were quite sustainable. The ecological and technical dimensions have a price of 60,89% and 63,47% respectively. Meanwhile, the social dimensions have all-time low value of 31,02% which is a smaller amount sustainable.